Analyzing Islamic Values Included in Kindergarten Rhymes in Jordan - Haroun, Ramzi; Alkhawaldeh, Naseer (Jordan Journal of Educational Sciences, 2005)
The study aimed at demonstrating the Islamic values included in kindergarten rhymes in Jordan by answering the following questions: 1-What are the Islamic values included in kindergarten rhymes in Jordan, and their percentages? 2- How could Islamic values included in kindergarten rhymes be categorized or classified?3- Which methods are used in presenting Islamic values to children? And to what extent these methods are appropriate to children’s characteristics?. To answer the previous questions, the researchers used the analytical approach. The analysis showed that rhymes included (28) Islamic values, of which some were appropriate for the age of the children. On the other hand, other rhymes included Islamic values which were not appropriate for the characteristics of children at this stage of development. In addition, the analysis showed that the most important Islamic values presented in children’s rhymes were those relating the child to his or her creator and significant people surrounding him or her such as parents. Finally, the analysis showed that most methods used to present Islamic values were inappropriate and in contrast to children’s characteristics. The study recommended that it be necessary to pay attention to the kinds of Islamic values presented to children, and to the methods used to present these values. Finally, the study emphasized that rhymes were appropriate moderators to teach children Islamic values at the kindergarten stage